Progressive idiopathic external root resorption in multiple teeth: A 6- year follow-up study) - Chowdhury, Shirin Sultana; Bashar, AKM (Update Dental College Journal, 2015)
This paper describes a case of progressive idiopathic external root resorption at cement-enamel junction in multiple teeth of both jaws ongoing for 6 years. In addition to clinical features serial radiographs are presented that revealed progressive involvement of root resorption. Since the first appointment until the next 6 years no clinical, radiographic or laboratory findings were available to disclose the etiology of such extensive ongoing resorption; neither the provided treatments could arrest the progression of the pathology that forced the clinicians to diagnose the case as progressive idiopathic external resorption. Update Dent. Coll. j: 2014; 4 (2): 14-19